Hambatan penerjemahan teks bahasa Arab ke dalam bahasa Indonesia: Pengalaman mahasiswa Sastra Arab Universitas Negeri Malang - Irhamni, Irhamni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This paper is intended to describe the results of a study focusing on students’ translation problems in translating Arabic texts into Indonesian. The problems result from students’ understanding and retelling (re-expressing) the results of that understanding during the translation process. In this study, the researcher applies a descriptive qualitative method. The results show that students’ problems in translation are closely related to (1) their understanding of linguistic and non-linguistic structures, and (2) their difficulties in retelling (re-expressing) the results of their reading regarding linguistic and non-linguistic issues.